High-risk human papillomavirus status and prognosis in invasive cervical cancer: a nationwide cohort study. Dataset 2 - Sparén, Pär (Karolinska Institutet, 2019)
High-risk human papillomavirus (hrHPV) infection is established as the major cause of invasive cervical cancer (ICC). However, whether hrHPV status in the tumor is associated with subsequent prognosis of ICC is controversial. We aim to evaluate the association between tumor hrHPV status and ICC prognosis using national registers and comprehensive human papillomavirus (HPV) genotyping.
In this nationwide population-based cohort study, we identified all ICC diagnosed in Sweden during the years 2002–2011 (4,254 confirmed cases), requested all archival formalin-fixed paraffin-embedded blocks, and performed HPV genotyping. Twenty out of 25 pathology biobanks agreed to the study, yielding a total of 2,845 confirmed cases with valid HPV results. Cases were prospectively followed up from date of cancer diagnosis to 31 December 2015, migration from Sweden, or death, whichever occurred first. The main exposure was tumor hrHPV status classified as hrHPV-positive and hrHPV-negative. The primary outcome was all-cause mortality by 31 December 2015. Five-year relative survival ratios (RSRs) were calculated, and excess hazard ratios (EHRs) with 95% confidence intervals (CIs) were estimated using Poisson regression, adjusting for education, time since cancer diagnosis, and clinical factors including age at cancer diagnosis and International Federation of Gynecology and Obstetrics (FIGO) stage.
Of the 2,845 included cases, hrHPV was detected in 2,293 (80.6%), and we observed 1,131 (39.8%) deaths during an average of 6.2 years follow-up. The majority of ICC cases were diagnosed at age 30–59 years (57.5%) and classified as stage IB (40.7%). hrHPV positivity was significantly associated with screen-detected tumors, young age, high education level, and early stage at diagnosis (p < 0.001). The 5-year RSR compared to the general female population was 0.74 (95% CI 0.72–0.76) for hrHPV-positive cases and 0.54 (95% CI 0.50–0.59) for hrHPV-negative cases, yielding a crude EHR of 0.45 (95% CI 0.38–0.52) and an adjusted EHR of 0.61 (95% CI 0.52–0.71). Risk of all-cause mortality as measured by EHR was consistently and statistically significantly lower for cases with hrHPV-positive tumors for each age group above 29 years and each FIGO stage above IA. The difference in prognosis by hrHPV status was highly robust, regardless of the clinical, histological, and educational characteristics of the cases. The main limitation was that, except for education, we were not able to adjust for lifestyle factors or other unmeasured confounders.
In conclusion, women with hrHPV-positive cervical tumors had a substantially better prognosis than women with hrHPV-negative tumors. hrHPV appears to be a biomarker for better prognosis in cervical cancer independent of age, FIGO stage, and histological type, extending information from already established prognostic factors. The underlying biological mechanisms relating lack of detectable tumor hrHPV to considerably worse prognosis are not known and should be further investigated.
Purpose:
To compile a comprehensive survival and HPV genotyping data and provide a large-scale population-based evaluation of the association between tumor high risk HPV status and prognosis of invasive cervical cancer.
This is an aggregated dataset (popmort_agg_2000_2015.dta) including the average survival rates of the Swedish female population, by age, for years 2000-2015. The dataset is generated based on the age-, gender- and calender year- specific survival rates of the Swedish population during the same calendar period.
The dataset included 4 variables:
• Sex: Gender (all female): 2=female.
• _age: Age (in years)
• _year: Calendar year
• Prob: Survival probability in corresponding age and calendar year

Humant papillomavirus av högrisk-typ (hrHPV) är den främsta orsaken till livmoderhalscancer. Huruvida förekomst av hrHPV-status i den invasiva tumörvävnaden har betydelse för prognosen är dock oklart.

Vi samlade in information om alla fall av invasiv livmoderhalscancer i Sverige under åren 2002-2011 (4254 bekräftade fall efter en fullständig journalgenomgång). Vi begärde ut motsvarande vävnadsblock för invasiv livmoderhalscancer från alla landets biobanker för att undersöka förekomst av humant papillomvirus (HPV). Tjugo av tjugofem tillfrågade biobanker lämnade ut vävnadsblocken, så att vi för totalt 2845 kvinnor med bekräftad invasiv livmoderhalscancer kunde analysera förekomst av HPV. Alla kvinnor med invasiv livmoderhalscancer följdes från datum för cancerdiagnos till dödsdatum (alla dödsorsaker) eller till och med den 31 december 2015.

Vi påvisade hrHPV i 2293/2845 (80,6 %) av tumörerna. Kvinnor med hrHPV-positiva tumörer var oftare screeningupptäckta, var yngre och hade en högre socioekonomisk status. De var också upptäckta i ett tidigare stadium jämfört med kvinnor med hrHPV-negativa tumörer. Den femåriga relativa överlevnaden för hrHPV-positiva fall var 74 % jämfört med den kvinnliga befolkningen i motsvarande ålder och under motsvarande kalenderår, medan den endast var 54 % för hrHPV-negativa fall. Efter att ha kontrollerat för ålder, tumörstadium vid diagnos och utbildningsnivå har de hrHPV-positiva fallen 39 %, högst signifikant, lägre överdödlighet jämfört med de hrHPV-negativa kvinnorna. Skillnaden var robust oavsett skillnader i kliniska egenskaper, histopatologisk tumörtyp eller kvinnans utbildningsbakgrund.

Status för hrHPV i invasiv tumörvävnad är således en stark och samtidigt rutinmässigt tillgänglig prognostisk biomarkör för prognosen av invasiv livmoderhalscancer. De underliggande biologiska mekanismerna till att avsaknad av detekterbar hrHPV i tumören leder till avsevärt sämre prognoser är inte kända och behöver undersökas ytterligare.

Syfte:

Att sammanställa nationella överlevnads- och HPV-genotypdata och utföra en storskalig populationbaserad utvärdering av sambandet mellan högrisk-HPV status och prognos för invasiv livmoderhalscancer.

Detta är en aggregerad dataset inklusive den genomsnittliga överlevnadsgraden för den svenska kvinnopopulationen, efter ålder, under åren 2000-2015. Datasetet genereras utifrån den svenska befolkningens ålder, kön och kalender årliga överlevnadsnivåer under samma kalenderperiod.
Förekomst av humant papillomvirus av högrisktyp och prognos för invasiv cervixcancer: en nationell kohortstudie. Dataset 2
Keywords: Prognosis; Prognos; population mortality; mortalitet; HEALTH; HÄLSA; Medical and Health Sciences; Medicin och hälsovetenskap